Qualitative changes of yoghurt prepared from milk preserved by different methods - Prasad V (Department of Dairy Science, College of Veterinary and Animal Sciences, 1990)
An experiment was conducted to study the qualitative changes of yoghurt prepared from milk preserved by different methods. An attempt was also made to study the efficiency of LP system in controlling psychrotrops in refrigerated milk thereby extending the keeping quality of such stored milk. The efficacy of the system was compared with pasteurized milk and raw milk stored under similar conditions. An exhaustive review of literature has been presented on the use of various preservation methods employed in milk, quality of yoghurt and other related aspects. The methods of analyses of some important components of milk and yoghurt has been detailed. The milk after collection were divided into three portions and used for various treatments A (raw milk as such), B (laboratory pasteurized) and C )LP activated). Samples in each treatment were again divided into four parts and stored under refrigeration for 0, 24, 48 and 72 hours for further analysis and yoghurt preparation. When raw milk was stored under refrigeration, acidity developed to a significantly high level (P < 0.05) at the end of 72 hours of storage whereas no significant increase in activity was noticed in treatments B and C. This result was corroborated by a decrease in both psychrotrophic and total bacterial counts in milk under treatments B and C. So it was concluded that the development of acidity in treatment A could be due to bultiplication of microbes particularly psychrotrophs. In B and C its growth was arrested by the treatments. Hydrogen peroxide and thiocyanate were detected in all raw milk samples at a level of 3.78 and 7.33 ppm respectively. The level of H2 O2 and SCN – used for the activation of LP system for the study were found to be adequate, since the psychrotrophic count in milk at the end of 72 hours in treatment C was less than that found in treatment B. The residual H2 O2 and SCN – contents at the end of 72 hours were found to be within the normal level found in milk thus having no health hazards, by this method of preservation. When yoghurt samples were prepared from stored milk no significant differences between treatments were noticed in the values of fermentation period, acidity, pH, total proteins and total solids. A significant increase in NPN and tyrosine values were noticed in yoghurt prepared from milk under treatment A indicating extensive proteolysis in milk during storage under this treatment. However, no difference was noticed between treatments B and C. Diacetyl and acetaldehyde were produced at a desirable level in yoghurt samples under all the three treatments. A proper ratio of Str. Thermophiles – 6 and L. bulgaricus – 4 was found to be maintained in all yoghurt samples. On organoleptic evaluation the yoghurt prepared from milk under treatment C could not be distinguished from other two treatments. In fact, yoghurt under C got a higher total score on organoleptic evaluation than A and B. Low score for body and texture, and falvour was observed under treatment A. This may be attributed to the effect of growth of psychrotrophs in raw milk during refrigeration. From the results, it was concluded that good quality yoghurt can be prepared from milk stored under refrigeration following pasteurization or LP activation. Yoghurt samples prepared from milk stored under treatment A was found to be of inferior quality when compared to B and C. The result also confirmed that LP system can be recommended as a safe preservative for extending storage life of refrigerated milk. When such stored milk was used for yoghurt production, no significant difference in the quality was noticed when compared to yoghurt under treatment B. Suggesting that LP activated milk can be conveniently and economically used for the production of fermented milk products like yoghurt without any apparent harmful effect.